REVIEW ON THE MONOGRAPH ”POPULATION OF THE REPUBLIC OF MOLDOVA AFTER 30 YEARS OF INDEPENDENCE” - Penina, Olga (Economy and Sociology, 2022)
The collective monograph “Population of the Republic of Moldova after 30 Years of Independence: Major Challenges and Policies Needed” is devoted to an exhaustive analysis of the population dynamics and the main demographic process in the light of socio-economic changes in the Republic of Moldova during the 30 years of independence. The authors underline that the process of depopulation associated with a rapid population ageing in Moldova cannot be solved solely by improving the country’s economic conditions. They consider that the reduction of migration, which is a key factor of depopulation in the country, is only possible with significant improvements in all aspects of people's lives. The recommendations addressed to policymakers are directly based on the results of the authors’ study, are clearly formulated and align with contemporary theoretical and practical concepts of demography. The monograph can be used as a guide for decision-makers in the process of developing and implementing public policies. One of the greatest strengths of the manuscript is the reliability of the statistical data used by the authors, including the own population estimates of the Centre for Demographic Research, which can sometimes differ significantly from officially published data.